Sedentary Behavior Is Only Marginally Associated with Physical Function in Adults Aged 40–75 Years—the Maastricht Study - van der Velde, Jeroen H. P. M.; Savelberg, Hans H. C. M.; van der Berg, Julianne D.; Sep, Simone J. S.; van der Kallen, Carla J. H.; Dagnelie, Pieter C.; Schram, Miranda T.; Henry, Ronald M. A.; Reijven, Petronella L. M.; van Geel, Tineke A. C. M.; Stehouwer, Coen D. A.; Koster, Annemarie; et al. (Frontiers in Physiology, 2017)
Background: In an ageing population, regular physical activity (PA) and exercise have been recognized as important factors in maintaining physical function and thereby preventing loss of independence and disability. However, (older) adults spent the majority of their day sedentary and therefore insight into the consequences of sedentary behavior on physical function, independent of PA, is warranted. Objective: To examine the associations of objectively measured sedentary time (ST), patterns of sedentary behavior, overall PA, and higher intensity PA (HPA) with objective measures of physical function. Methods: This is a cross-sectional study in 1,932 men and women (aged 40-75 years) participating in The Maastricht Study. The activPAL3 was used to assess daily sedentary behavior: ST (h), sedentary breaks (n), prolonged (≥30min) sedentary bouts (n), and to assess time spent in (H)PA (h). Measures of physical function included: covered distance during a six minute walk test (6MWD (meters)), timed chair rise stand test performance (TCSTtime (seconds)), grip strength (kg kg 1), and elbow flexion and knee extension strength (Nm kg 1). Linear regression analyses were used to examine associations between daily sedentary behavior and PA with physical function. Results: Every hour ST was associated with shorter 6MWD (B= -2.69 m (95% CI= -4.69;-0.69)) and lower relative elbow extension strength (B= -0.01 Nm kg-1 (-0.02;0.00). More sedentary breaks were associated with faster TCSTtime: B= -0.55 s (-0.85;-0.26). Longer average sedentary bout duration was associated with slower TCSTtime (B= 0.17 s (0.09;0.25)) and lower knee extension strength (B=-0.01 Nm kg-1(-0.02;0.00)). Every hour of PA and HPA were associated with greater 6MWD (BPA= 15.88 m (9.87;21.89), BHPA= 40.72 m (30.18;51.25)), faster TCSTtime (BPA= -0.55 s (-1.03;-0.07), BHPA= -2.25 s (-3.09;-1.41)), greater elbow flexion strength (BPA=0.03 Nm kg-1 (0.01; 0.07)), (BHPA=0.05 Nm kg-1 (0.01;0.08)), and greater knee extension strength (BPA= 0.04 Nm kg-1 (0.01; 0.07)), (BHPA= 0.13 Nm kg-1 (0.06;0.20)). Conclusion: In adults aged 40-75 years, sedentary behavior appeared to be marginally associated with lower physical function, independent of HPA. This suggests that merely reducing sedentary behavior is insufficient to improve/maintain physical function. In contrast, engaging regularly in PA, in particular HPA, is important for physical function.